An Explorative Study on Intensity of Reciting Al-Quran and Level of Exam Anxiety among Medical Students - Taqiudin Miftakhurrohman; Sinu Andhi Jusup; Dian Nugroho (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Exam has become a major factor which cause anxiety among medical students. Reciting Al-Quran has therapy effect for reducing the level of anxiety. This study aimed to understand the perception of the students about the effect of reciting Al-Quran to exam anxiety in medical students of Sebelas Maret University. Methods: The study used qualitative research with phenomenological approach. Data was collected by focus group interview method. The respondents were twenty moslem medical students of Sebelas Maret University. Method for collecting data was done by purposive sampling. The respondents were grouped according to gender. Analysis of the data in this study was content analysis. Result: All respondents considered that it was necessary to do preparation for exam. The lack of preparation would evoke exam anxiety during pre-exam period and exam period. Anxiety was also caused by environment factor and worriness of exam result. Respondents experienced low level of anxiety. It was indicated by psychologic and somatic symptom, without severe problem. A few efforts were done for reducing exam anxiety, including academic aspect like studying and spirituality aspect like improve praying, especially reciting Al-Quran. All respondents agreed that reciting Al-Quran was able to reduce anxitety at every condition. Factors that could reduce anxiety were quality and quantity during reciting Al-Quran. Conclusion: Exam anxiety was often happened in medical students. Reciting Al-Quran regularly can reduce the exam anxiety. Keywords: exam anxiety, intensity, reciting Al-Quran, medical student